Małe i średnie przedsiębiorstwa w polskiej i czeskiej części Euroregionu Nysa - wybrane uwarunkowania prawno-ekonomiczne - Kurková, Karina (Small and Medium Enterprises in Polish and Czech Part of Neisse Euroregion - Selected Legal and Economic Condition, 2005)
Appearance of the new member countries in the European Union created the new reality, among others, for enterprises to function. These are new challenges, chances, but also increased competition and struggle for the market. They will affect mainly small and medium enterprises though they have the biggest predispositions to adjust - to overcome difficulties and take those chances. The present article focuses mainly on comparison of selected legal and economic conditions connected with running business activity by small and medium enterprises after 1 May 2004.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 197-207